Inferences from COVID-19 post-exposure risk assessment of health care workers in the pre-vaccination era at a major COVID sentinel center, Sri Lanka - Dammalage L. Bhagya Piyasiri; Wijayawardhene Ganaka G. Senaratne; Pathirawasam Krishantha Jayasekera; Vigeetha H. Withanage; Nayomi S. Danthanarayana; Harshanie A. Ubeysekara; Kankanamge D. Dulnie S. Wijeweera (Public Library of Science (PLoS), 2023)
Despite the hospital triage system trying to prevent COVID-19 patients from getting admitted to wards other than isolation/quarantine units, COVID-19 patients were accidentally being discovered time to time from non-COVID-19 wards due to atypical or asymptomatic presentations. Consequently, post-exposure risk assessment was carried out for the relevant health care workers (HCW) and the other patients to assess their risk level of acquiring COVID-19, and to quarantine them if concluded as high risk. Hence, the objective of the study was to assess the outcome and the adequacy of COVID-19 post-exposure risk assessment of health care workers which would be useful in future outbreaks. We studied all events of accidental detection of COVID-19 patients happened in non-COVID-19 wards which were leading to subsequent risk assessment using the 5-questions based tool adapted from the WHO recommendations. The 5 questions discussed the protective measures during face to face meetings or in physical contacts, protective measures during aerosol generating procedures, splashes onto the face, and hand hygiene measures. A retrospective cross-sectional study carried out in the Teaching Hospital Karapitiya, Galle, Sri Lanka, for 4 months covering the second wave of the pandemic. Hospital data base of risk assessments was accessed anonymously and the "yes" or "no" responses to the 5-questions assessment tool were analysed. There were 62 events involving 891 health care workers who underwent post-exposure risk assessment. From the responses the highest score of "yes" was recorded against question 3 (25.7% of total "yes" answers for all questions and 5.8% of total answers for the question number 3) revealing inadequate precautions taken by HCWs in aerosol generating procedures. Hundred and sixty two (18.2%) HCWs were quarantined as high risk and only one became positive for COVID-19 during the quarantine period. Though the 5-question based risk assessment tool effectively helps to identify breaches in infection control during an exposure to a positive COVID-19 patient, it may not be adequate at times as the only tool in deciding the assessee's risk level.